2015
DOI: 10.1515/ijafr-2015-0013
|View full text |Cite
|
Sign up to set email alerts
|

A note on challenge trials to determine the growth of Listeria monocytogenes on mushrooms (Agaricus bisporus)

Abstract: In the EU, food is considered safe with regard to Listeria monocytogenes if the number of micro-organisms does not exceed 100 colony forming units (cfu)/g throughout its shelf-life. Therefore, it is important to determine if a food supports growth of L. monocytogenes. Guidelines for conducting challenge tests for growth assessment of L. monocytogenes on foods were published by the European Union Reference Laboratory (EURL) in 2014. The aim of this study was to use these guidelines to determine if refrigerated,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…They demonstrated that both sliced and whole mushrooms supported growth of L. monocytogenes. In a subsequent experiment, Leong, Alvarez-Ordóñez and Jordan (2015) have shown that, using a different inoculation procedure (surface spread rather than dipping), whole mushrooms did not support growth of L. monocytogenes.…”
Section: Challenge Tests In Vegetables and Saladsmentioning
confidence: 93%
“…They demonstrated that both sliced and whole mushrooms supported growth of L. monocytogenes. In a subsequent experiment, Leong, Alvarez-Ordóñez and Jordan (2015) have shown that, using a different inoculation procedure (surface spread rather than dipping), whole mushrooms did not support growth of L. monocytogenes.…”
Section: Challenge Tests In Vegetables and Saladsmentioning
confidence: 93%
“…A subsequent study showed that A. bisporus does not support the growth of L. monocytogenes (Leong et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, further measures to help control L. monocytogenes in the growth substrates and environment are needed in order to reduce the risk of mushroom contamination (Leong et al . , ; Viswanath et al . ; Akata et al .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, while there are some inactivation/control procedures in place to control L. monocytogenes, there is also ample opportunity for recontamination of the growing substrates and contamination of the growing environment once the substrate preparation procedure is complete. Therefore, further measures to help control L. monocytogenes in the growth substrates and environment are needed in order to reduce the risk of mushroom contamination (Leong et al 2013(Leong et al , 2015Viswanath et al 2013;Akata et al 2015;Murugesan et al 2015).…”
Section: Introductionmentioning
confidence: 99%